Model-driven development of web applications with UWA, MVC and JavaServer Faces - Distante, Damiano; Canfora, Gerardo; Rossi, Gustavo Héctor; Pedone, Paola (2007)
This paper presents a model-driven approach to the development of web applications based on the Ubiquitous Web Application (UWA) design framework, the Model-View-Controller (MVC) architectural pattern and the JavaServer Faces technology. The approach combines a complete and robust methodology for the user-centered conceptual design of web applications with the MVC metaphor, which improves separation of business logic and data presentation. The proposed approach, by carrying the advantages of Model-Driven Development (MDD) and user-centered design, produces Web applications which are of high quality from the user's point of view and easier to maintain and evolve. Keywords: Web Engineering, Model-Driven Development, Model Transformation, Model Driven Architecture, UWA, UML, MVC, JavaServer Faces.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 12 nov. 2008)
Proceedings of ICWE 2007, Springer Verlag LNCS, 2007.
Keywords: JAVASERVER FACES - JSF; ARQUITECTURA DIRIGIDA POR MODELOS - MDA; DESARROLLO DE SOFTWARE DIRIGIDO POR MODELOS - MDD; DISEÑO CENTRADO EN EL USUARIO; DESARROLLO DE APLICACIONES WEB